Diseño de una herramienta informática para la gestión de los riesgos ambientales y de la SST en un Sistema Integrado de Gestión, para MiPymes del sector de confección textil. (2019)
The purpose of this degree work was the design and construction of a computer tool to manage the risks of OSH and environmental impacts to companies (MSMEs and SMEs) of the textile apparel sector in Colombia. That was proposed, based on information collected on the difficulty that some of the companies presented to manage their risks and impacts optimally. In order to fulfill the objective, an exhaustive bibliographic review and subsequent visit to 5 different companies in the textile manufacturing sector in the city of Bogotá were necessary. During the visits, it was possible to identify that many of the companies are not yet managing their OSH Risks or Environmental Impacts, and those that, if they are doing so, expressed disinterest and nonconformity with the issue. For the above, the computer tool was designed, based on the identification of the context of the sector that can be landed to each company, subsequently the identification of OSH Hazards and Environmental Aspects was carried out, to subsequently apply the methodology for assessing the Risks of the OSH (GTC45: 2012) and propose the methodology of Environmental Impact assessment applied to the complexity of the sector, based on a guide provided in the environmental module of the specialization. Finally, the menu of controls for the Management of Risks of the OSH and of the Environmental Impacts applicable to the sector were proposed, which can be selected by each user according to the management capacity of each organization.